1997
DOI: 10.1161/01.hyp.30.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine Oxidase Inhibition With Oxypurinol Improves Endothelial Vasodilator Function in Hypercholesterolemic but Not in Hypertensive Patients

Abstract: Hypercholesterolemic and hypertensive patients have impaired endothelium-dependent vasorelaxation because of decreased nitric oxide activity, but the mechanism underlying this abnormality is unknown. This study sought to determine whether an increased breakdown of nitric oxide by xanthine oxidase-generated superoxide anions could participate in these forms of endothelial dysfunction. We studied vascular responses to intrabrachial infusion of acetylcholine (an endothelium-dependent vasodilator, 7.5 to 30 microg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
132
5
5

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(150 citation statements)
references
References 35 publications
8
132
5
5
Order By: Relevance
“…In these subjects, eXO activity was increased by Ͼ200% compared with age-matched controls. This finding is in line with the observations of Cardillo et al, 22 who demonstrated that inhibition of XO improved endotheliumdependent vasodilation in subjects with hypercholesterolemia.…”
Section: Discussionsupporting
confidence: 93%
“…In these subjects, eXO activity was increased by Ͼ200% compared with age-matched controls. This finding is in line with the observations of Cardillo et al, 22 who demonstrated that inhibition of XO improved endotheliumdependent vasodilation in subjects with hypercholesterolemia.…”
Section: Discussionsupporting
confidence: 93%
“…2 This is underscored by the observation that administration of scavengers of reactive oxygen species can improve NO bioavailability in hypercholesterolemia. [41][42][43] Our data support the notion that in the early phase of atherosclerosis, ie, in the presence of hypercholesterolemia, decreased NO bioavailability is probably indeed a multifactorial phenomenon, which cannot only be explained by impaired NO production.…”
Section: Discussionsupporting
confidence: 84%
“…36 -38 One major source of superoxide production in hypercholesterolemia appears to be xanthine oxidase; inhibitors of this enzyme reduced endothelial superoxide production in vitro 38 and restored endothelial dysfunction in vivo. 41 Another source is NOS itself, which may exhibit uncoupling of L-arginine oxidation. 2 This is underscored by the observation that administration of scavengers of reactive oxygen species can improve NO bioavailability in hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experimental data directly implicate UA in endothelial dysfunction (18,19), but few studies were conducted in humans and available data are controversial. In patients with heart failure (20), with type 2 diabetes (21), at increased cardiovascular risk (10), and with hypercholesterolemia but not in patients with essential hypertension (22), allopurinol, a xanthine oxidase inhibitor that lowers UA and interacts with anion superoxide generation (23), improves endothelial dysfunction. In the study of Mercuro et al (10), the beneficial effect of allopurinol could have been a direct consequence of the reduced UA levels rather than of superoxide anions mediated by xanthine oxidase inhibition because of the close correlation found between the amount of that decrease and the improvement of endothelial function.…”
Section: Discussionmentioning
confidence: 99%